Measuring persistent effects of circumstances and inequality of opportunity using panel data - Gaurav Datt; Ravisha Wellappuli; John Nguyen; Arturo Martinez; Joseph Albert Nino Bulan (Asian Development Bank (ADB), 2024)
In this paper, we make two contributions to the literature on inequality of opportunity (IOP). First, we use longitudinal data for two developing countries, Thailand and Viet Nam, to study the evolution of absolute and relative IOP in the income and consumption space over a 10-year period, thus adding to the relatively limited evidence on changes in IOP over time. Second, we propose and estimate "circumstance" elasticities as measures of the responsiveness of current income and consumption to pre-existing circumstances. Our analysis finds that inequalities of opportunity are enduring in both countries. We also find that the circumstance elasticities for the vast majority of household types identified by their baseline circumstances are not significantly different to unity and non-declining over time. Our evidence points to long-duration effects of circumstances on welfare outcomes.
Keywords: D31; D63; O15; 330; inequality of opportunity; circumstance elasticity